METHODOLOGICAL KNOWLEDGE IN THE CONTEXT OF NATURAL EDUCATION IN MODERN SCHOOL - Halatyuk, Yury; Halatyuk, Taras (Educological discourse, 2018)
The article analyzes the place and role of methodological knowledge in the system of natural education of the modern school. It is shown that methodological knowledge is an important didactic category, an integral criterion for the effectiveness of natural education. School natural science has a powerful didactic potential for the formation of methodological knowledge. There is a close link between methodological knowledge and creative learning activities. Methodological knowledge is a means and product of creative bulk-cognitive activity. Creative educational and cognitive activity is an effective mechanism for the formation of methodological knowledge. Creative educational and cognitive activity of students is an activity directed by a teacher with the help of the appropriate system of educational means; is aimed at formulating problems and performing creative tasks; provides for the search and explanation of natural relationships and relations of observable facts, phenomena, processes through the application of methods of scientific methods of cognition, as a result of which students discover new knowledge and actively acquire them, get acquainted with the methodology of scientific knowledge, develop cognitive skills and skills, form cognitive motives and organizational qualities. The priority of the creative function of teaching is a necessary didactic condition for the formation of methodological knowledge in the process of studying natural subjects in a modern school. The nomenclature of methodological knowledge and cognitive abilities, which determine the effectiveness of creative educational activity and is at the same time its product, is determined.